2021
DOI: 10.1002/bes2.1924
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Ecological Knowledge and Inclusive Pedagogy Increase Retention and Success Outcomes of STEM Students

Abstract: The i‐NATURE (Indigenous iNtegration of Aquatic sciences and Traditional Ecological Knowledge for Undergraduate culturally Responsive Education) is a culturally relevant, project‐, and place‐based curriculum that included extensive applied research experience contextualized for specific Indigenous communities. The program developed a model for incorporating Traditional Ecological Knowledge into STEM undergraduate education which included direct participation of several Indigenous communities in the Pacific Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 80 publications
(97 reference statements)
0
8
0
Order By: Relevance
“…Native American undergraduate students are a subset of underrepresented minority students in the sciences in the United States, with pervasive socioeconomic barriers to success in the university context (Alexiades et al, 2021 ). Consistent with objective (1), we are currently evaluating existing data science and EF resources to address the accessibility of EF education for Native American undergraduate students.…”
Section: Discussion and Recommendations For Next Stepsmentioning
confidence: 99%
“…Native American undergraduate students are a subset of underrepresented minority students in the sciences in the United States, with pervasive socioeconomic barriers to success in the university context (Alexiades et al, 2021 ). Consistent with objective (1), we are currently evaluating existing data science and EF resources to address the accessibility of EF education for Native American undergraduate students.…”
Section: Discussion and Recommendations For Next Stepsmentioning
confidence: 99%
“…Their findings indicated an increase in academic performance and graduation rates. Alexiades et al (2021) created a culturally responsive undergraduate STEM course that allowed the integration of traditional ecological knowledge from indigenous groups and found it led to an increase in mean grade point average. In support of the first research question posed in this study, they also found students had an increased interest in pursuing a career in STEM.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, acknowledgement and research into the experiences of emerging multilingual are continually growing. In addition, we acknowledge the marginalization of Native American/Indigenous/Alaskan Native and First Nations in the sciences and current efforts to develop inclusive pedagogies, implement culturally relevant curricula, and use local and indigenous knowledge in science instruction (Aikenhead, 1997; Alexiades et al, 2021; Reano & Ridgway, 2015). Implications for science instruction for these students have more advanced research and wider dissemination.…”
Section: Existing Disparities In Who Has Access To Quality Science In...mentioning
confidence: 99%